Human recombinant galectin-1 produced by transplantomic tabacco plants - Vater, Catalina Francisca (2019)
Transplastomic plants stand out from other molecular farming platforms because of the highly efficient production of recombinant proteins(>50% of the total soluble protein). In some cases, however, low and even undetectable levels of heterologous protein expression have beenreported in this system. This fact makes it necessary to evaluate and study the expression system whenever a new protein emerges as a candidateto be produced using this platform.